2016
DOI: 10.1016/j.plefa.2016.03.015
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized, double blind, placebo-controlled evaluation of the effects of eicosapentaenoic acid and docosahexaenoic acid on the clinical signs and erythrocyte membrane polyunsaturated fatty acid concentrations in dogs with osteoarthritis

Abstract: This study demonstrated that the daily supplementation of a dogs diet with EPA and DHA shifts the blood fatty acid concentrations correlating to relief of clinical signs associated with OA in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 37 publications
1
42
0
1
Order By: Relevance
“…PUFAs have anti-inflammatory and antioxidative properties (Bento et al, 2011;Mehler et al, 2016;Morin et al, 2015;Nobre et al, 2013;Paterniti et al, 2014;Pineda-Peña et al, 2018;Türkez et al, 2012;Wohlers et al, 2003). In the carrageenan-induced paw edema test, a DHA-rich diet for 15 days reduced inflammation (Nakamura, Hamazaki, Kobayashi, & Yazawa, 1994).…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…PUFAs have anti-inflammatory and antioxidative properties (Bento et al, 2011;Mehler et al, 2016;Morin et al, 2015;Nobre et al, 2013;Paterniti et al, 2014;Pineda-Peña et al, 2018;Türkez et al, 2012;Wohlers et al, 2003). In the carrageenan-induced paw edema test, a DHA-rich diet for 15 days reduced inflammation (Nakamura, Hamazaki, Kobayashi, & Yazawa, 1994).…”
Section: Discusionmentioning
confidence: 99%
“…n‐3 (fish oil) and n‐6 (soybean oil) PUFA‐rich diets can also reduce carrageenan‐induced paw edema in rats indicating anti‐inflammatory effects (Nobre et al, ; Wohlers, Nascimento, Xavier, Ribeiro, & Silveira, ) while DHA reduced spinal cord inflammation in rat (Paterniti et al, ). Daily supplementation diet with eicosapentaenoic acid and DHA reduced clinical signs associated with osteoarthritis in dogs (Mehler, May, King, Harris, & Shah, ) and in humans; fish oil supplement usage in patients with rheumatoid arthritis were more likely to reduce use of nonsteroidal anti‐inflammatory drugs (NSAIDs) and to be in remission than patients who did not use fish oil (Cleland, Caughey, James, & Proudman, ). A meta‐analysis of n‐3 fatty acids and pain indicated that fish oil reduces patient‐assessed joint pain and use of NSAIDs in patients with rheumatoid arthritis (Goldberg & Katz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Academic and private practice veterinary medicine can provide valuable biomedical research data, as referral centres are often equipped with MRI and CT scanners, arthroscopes and state-of-theart pathology and molecular diagnostic capabilities. Academic veterinary centres also pilot advances in the use of anti-inflammatory and pain-modulating OA drug therapies 10,14,15 . In this Review, we summarize research relating to common forms of spontaneous dog OA, focusing on the presentation and genetics of analogous diseases of the hip and knee, within a framework of human OA phenotypes.…”
mentioning
confidence: 99%
“…It is known that chondrocytes have only limited access to nutrients due to the avascular, dense and negatively charged matrix (Villalvilla, Gómez, Largo, & Herrero‐Beaumont, ). However, feeding studies provide evidence that diets rich in n‐3 fatty acids alter the fatty acid composition in canine serum (Barrouin‐Melo et al., ; Hall, Picton, Skinner, Jewell, & Wander, ; Mehler et al., ) and that fatty acids are generally transported to the joints bound to albumin or lipoproteins (Arkill & Winlove, ). To mimic the process of fatty acid transport, we included 5% of FCS in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Several feeding studies (Fritsch et al., ; Mehler, May, King, Harris, & Shah, ; Moreau et al., ; Roush et al., ) have suggested that dietary supplementation with marine n‐3 fatty acids is beneficial in the treatment of canine OA. Two classes of essential polyunsaturated fatty acids (PUFA) are important as part of a healthy dog diet: the n‐6 fatty acids, for example, arachidonic acid (AA), which are present in meat and vegetable oils, and the n‐3 fatty acids, for example, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), which both are found predominantly in marine feed.…”
Section: Introductionmentioning
confidence: 99%